Metastasis of ovarian cancer to nasal skin and skin on the trunk: a rare case report - Chen, Chen; Yingyao, Ouyang; Yan, Xiang; Qianru, He; Hong, Wang; Chen, Chen; Lei, Yang (Frontiers in Oncology, 2023)
Cutaneous metastases of ovarian cancer are rare and often have poor prognosis. We report a case of a 62-year-old woman with recurrent low-grade serous ovarian cancer, who presented with lung, brain, and multiple skin (nasal and anterior chest wall) metastases approximately six months after the initial diagnosis. In this case, Nijmegen breakage syndrome carrier status caused by RAD50 heterozygous mutation and previous bevacizumab therapy could be the predisposing factor for cutaneous metastases. The patient was treated with local radiotherapy (nasal skin and brain, 30Gy/6f/1.2W) and three courses of chemotherapy with albumin-bound paclitaxel and carboplatin, resulting in drastic remission of the cutaneous metastases. Unfortunately, treatment interruption resulted in rapid tumor progression, followed by death. This case represents an interesting example of cutaneous metastasis of ovarian cancer with rare clinical manifestations, unique genetic mutations, and reasonable response to treatment. Chemoradiotherapy might be an appropriate option for cutaneous metastases of ovarian cancer. Nevertheless, we still hope to find out the best treatment strategy after collecting and reviewing more cases in the future.